2018
DOI: 10.1111/jbfa.12342
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐border acquisitions and host country competitiveness

Abstract: We investigate the competitive effects of cross‐border takeovers and find that following the acquisitions, the competitiveness of cross‐border targets improves. The results for industry rivals, however, are mixed. Rivals of targets of cross‐border acquisitions experience improvements in their competitive position in the long term, while at the same time, their growth and market share suffer. These acquisitions lead to a shifting of market share from rivals to cross‐border targets, which is suggestive of increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 72 publications
2
4
0
Order By: Relevance
“…Model 2 in Table 6 shows that on takeover announcement, the coefficient for the target CAR variable is 0.114, which is significantly different from zero. This rejects hypothesis 1 and is consistent with prior literature (Eckbo, 1983, 1985—for domestic MA Otchere & Oldford, 2018—for cross‐border M&A) that rival firms to a target, on average, benefit in a takeover bid. The other control variables are largely insignificant, with a few notable exceptions.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Model 2 in Table 6 shows that on takeover announcement, the coefficient for the target CAR variable is 0.114, which is significantly different from zero. This rejects hypothesis 1 and is consistent with prior literature (Eckbo, 1983, 1985—for domestic MA Otchere & Oldford, 2018—for cross‐border M&A) that rival firms to a target, on average, benefit in a takeover bid. The other control variables are largely insignificant, with a few notable exceptions.…”
Section: Resultssupporting
confidence: 89%
“…The overall sectoral losses are also consistent with politicians’ biases highlighted by Seabright (2005), which include a tendency to support high‐tech sectors irrespective of the country's comparative advantage, failure to account for the impact of favoring one firm on the other firms and a lack of willingness to let poor investments fail, which is an important part of innovation and discovery. The overall sectoral losses at bid failure are also consistent with Otchere and Oldfeld (2018) who find that the cross‐border M&A activity benefits the sector and country by making them more competitive despite short‐term pressure on rivals’ margins.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Bertrand and Zitouna (2008) observed improvements in productivity. Similarly, Otchere and Oldford (2018) demonstrated that the competitiveness of target firms increased following an acquisition.…”
Section: Literature Reviewmentioning
confidence: 97%